Vorhersage von Produktausbeuten für unterschiedliche Reaktortypen bei der katalytischen Pyrolyse. Issue 5 (22nd March 2018) - Engelhardt, Armin; Stam‐Creutz, Timo; Hahn, Thomas; Seitz, Mathias
Abstract: For the change to a post‐fossil society, raw material‐variable processes like catalytic cracking (catalytic pyrolysis) of solid hydrocarbons are needed. For the prediction of the product yield from different feedstocks, model approaches have been developed, taking into account raw material quality, catalyst properties, and process conditions. A good description of the substantial use of lignite is possible with few influencing variables and significant model parameters. Perspectively, these models will be transferred to the cracking of polyolefinic recyclates and fat‐rich biomass.